2014
DOI: 10.1128/aem.00493-14
|View full text |Cite
|
Sign up to set email alerts
|

Use of Silicate Minerals for pH Control during Reductive Dechlorination of Chloroethenes in Batch Cultures of Different Microbial Consortia

Abstract: In chloroethene-contaminated sites undergoing in situ bioremediation, groundwater acidification is a frequent problem in the source zone, and buffering strategies have to be implemented to maintain the pH in the neutral range. An alternative to conventional soluble buffers is silicate mineral particles as a long-term source of alkalinity. In previous studies, the buffering potentials of these minerals have been evaluated based on abiotic dissolution tests and geochemical modeling. In the present study, the buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 50 publications
2
26
0
Order By: Relevance
“…Moreover, silicates are likely interacting with the pH probe glass membrane. Such a difficulty can be circumvented by assessing acidity function measurements and using spectrocolorimetry [46,47].…”
Section: Protonation Of the Silicate Chainsmentioning
confidence: 99%
“…Moreover, silicates are likely interacting with the pH probe glass membrane. Such a difficulty can be circumvented by assessing acidity function measurements and using spectrocolorimetry [46,47].…”
Section: Protonation Of the Silicate Chainsmentioning
confidence: 99%
“…The detection of large amounts of methane at these locations, combined with the proven presence of the full OHR potential, indicated that the partial degradation of PCE was not a consequence of a lack of available electron donor (Table S5). A closer look at other variables showed that pH-values at wells NA-1 and NA-6 dropped to low values around 5.0-5.5, which are known to severely impede cisDCE and VC dechlorination (Lacroix et al, 2014). Overall, the pH was in general below 7.0 at all wells, probably a consequence of the mineralogical composition of the bedrock at this site, which is formed by minerals such as biotite, an iron-and manganese silicate, providing a weak pH-buffering capacity.…”
Section: Site B-monitoring Of Reductive Dechlorination During An Erdmentioning
confidence: 99%
“…The results showed that pH in the cultures supplemented with 5 to 20 mM glucose decreased from 5.1 to 5.9 after 20 days, while the pH was maintained between 6.6 and 6.9 with the addition of 0.5 or 2.5 mM of glucose. Inhibitory effect of acidic conditions on reductive dehalogenation has been previously reported (Lacroix et al, 2014), while glucose itself had no effect on the debromination (SM Fig. S3).…”
mentioning
confidence: 83%